리츠제도 활성화를 위한 실증분석 - 조상배(Jo, Sang Bae); 권대중(Kwon, Dae Jung) (대한부동산학회지, 2018)
본 연구는 부동산 간접투자 제도인 리츠를 통해서 부동산 간접투자 시장을 활성화하고 투자자들이 부동산시장에 원활히 참가할 수 있도록 제도에 대한 전반적인 문제점을 도출하고 개선방안과 활성화를 위한 정책을 제언하기 위한 것이다. 부동산 간접투자의 본질은 다수의 투자자로부터 자금을 모아 부동산 등에 투자하여 그 수익을 투자자에게 돌려주는 투자수단이다. 본 연구는 우리나라의 리츠 제도가 활성화되지 못한 원인이 무엇인지 실증연구를 통해서 규명하기로 하였다. 실증분석에서 추출된 문제점은 첫째, 부동산 간접투자 규제 완화의 문제점으로 리츠의 제도 진입 등이 문제점으로 지적되고 있다. 둘째, 리츠 활성화의 문제점으로 세제 혜택, 공모 활성화 등이 발견되었다. 이상의 문제점을 근거로 개선방안을 연구하였으며, 그 결과 리츠 제도의 개선방안을 아래와 같이 제시하였다. 첫째, 규제 완화에 대한 세부사항은 리츠의 제도 진입은 영업인가제를 등록 또는, 신고제로 전환해야 하며, 둘째, 활성화에 대한 세부사항은 세제 혜택이 필요하며, 종합부동산세의 감면이 필요하다. 양도소득세의 제도개선으로 업 리츠의 도입 등이 필요하다. 본 연구는 부동산 간접투자 제도인 리츠가 직면한 문제점과 이에 대응하는 개선방안을 제시하여 부동산 간접투자제도의 선진화를 지원하고자 한다. This study is designed to stimulate the real estate indirect investment market through the real estate indirect investment system, the REITs, and to identify and address overall issues and improve policies on the system to enable investors to participate in the real estate market. The essence of indirect real estate investment is the means of investing money from a large number of investors in real estate and then returning the profits to the investor. The problem extracted from the empirical analysis is pointed out to be the entry of REITs as a problem to ease regulations on real estate investment. Second, tax benefits and the activation of public subscription were discovered as problems in the activation of the REITs. Based on the above problems, improvement measures were studied, and as a result, the improvement measures of the REITs were proposed as follows. First, the details of deregulation must change the entry of REITs to register or report their own business, and second, the details of activation will need tax benefits and a comprehensive real estate tax reduction will be needed. As a result of the improvement of the system of capital gains taxes, the introduction of the business trust is needed. This study aims to support the advancement of the real estate indirect investment system by presenting the problems faced by the real estate indirect investment system, the REITs, and corresponding improvement measures. KCI Citation Count: 1